PENYEBARAN LUBANG GEREK SERANGAN RINTISAN KUMBANG AMBROSIA PADA DOLOK KARET YANG DIKULITI - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The distribution of initial tunnel of ambroisa beetle infestations on debarked rubber logs was studied. The surface. of the test logs was plotted into 8 equal beds, including two single beds situated on the top and bottom, and three pair- ed others situated on the upper sides, sides, and under sides. Intensity of the beetle tunnels on each bed was observed four times at the day of 11, 13, 17, and 21 after the debarking.It was shown that the ambrosia beetle tunnels were not equally scattered on the entire parts of the log surface.The two paired plots, sides and upper sides, were most susceptible ones eventhough the intensity of the tunnels vari- ed during the observation periods. The lower susceptible plots were respectively recorded on the top, under sides and bottom part of the logs.